Harlequin in Hogtown : George Luscombe and Toronto Workshop Productions - Carson, Neil (University of Toronto Press, 1995)
From the beginning, Luscombe envisaged his new company as part of an international contingent of artists determined to further the cause of socialism through art. He saw himself as part of a tradition which sought to bring about change by 'educational' rather than political or revolutionary means ... Unfortunately, Canadian audiences, unlike their counterparts in Russia, Germany, or England, appeared to be stubbornly indifferent to live theatre.